AN ANALYSIS OF FIGURATIVE LANGUAGE TRANSLATION IN MARK TWAIN'S NOVEL ENTITLED ADVENTURES OF HUCKLEBERRY FINN - GRAHAPRILWANA (2009)
This paper entitled An Analysis of Figurative Language Translation in Mark Twain's Novel Entitled Adventures of Huckleberry Finn. The aims of this research are to investigate kinds of figurative language in the novel, to investigate the procedures used by the translator in translating figurative language, and to judge the quality of the translated version of the figurative language. This research paper was conducted by using qualitative method through applying several stages. The first one was by studying the both novel the English version and translated version. The second one was by collecting and categorizing the data which is in the form of figurative language based on each characteristic from selected chapters. The third one was by analyzing the gained data in terms of the translation procedures proposed by Larson (1988) which were applied to every type of figurative language. Finally, by analyzing and judging the gained data in terms of accuracy, clarity and naturalness. The result of the research indicated that there were 15 types of figurative language found in the selected chapters in the novel. Those were 121 figurative language which comprise simile (31 items), imagery (25 items), hyperbole (21 items), idiom (11 items), personification (8 items), paradox (6 items), symbol (4 items), metaphor (3 items), onomatopoeia (3 items), allusion (2 items), irony (2 items), metonymy (2 items), alliteration (1 item), assonance (1 item), and synecdoche (1 item). Several procedures were applied by translator in translating figurative language. They were synonymy (25 items), through translation (24 items), transposition (16 items), paraphrase (11 items), expansion (11 items), transference (8 items), reduction (7 items), naturalization (5 items), modulation (5 items), notes, addition and glosses (3 items), cultural equivalent (3 items), descriptive equivalent (2 items), and literal translation (1 item). The findings showed that the translators are generally acceptable, understandable, and suitable despite their slight of naturalness. Based on the elaborations above, it can be concluded that simile was the most frequently found in the novel, synonymy was the most frequently procedure applied in translating figurative language in the novel and the translations are generally has fulfilled the criteria of good translation proposed by Barnwell, namely, accuracy, clarity, and naturalness.